Pelatihan Pembuatan Modul Ajar Inovatif Sesuai Tuntutan Kurikulum Merdeka di Desa Serdang - Situmorang, Adi Suarman; Br Sinaga, Juli Antasari; Sihombing, Dame Ifa; Sauduran, Golda Novatrasio (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
This community service activity aims to train teachers in Serdang village, Beringin sub-district in designing innovative teaching modules according to the demands of the independent curriculum, which will be implemented in October-November 2023 with partners as the principal of SD Negeri 101917 and the head of Serdang village, Beringin sub-district, Deli district. Serdang. The location of the activity was held at the Serdang Village meeting office with a capacity of 80 participants. The results of the activities obtained from observations show that the overall achievement of the goals that have been set appears to be in the "very good" category because the indicator value (I) = 4.603 ≥ which means that the activity implementation process has been carried out well. From the evaluation results of PkM activities, it can also be seen that there is a decrease from the evaluation results during PkM activities to the evaluation results after PkM activities, namely from an average of 90.86% down to an average of 89.79%. From the results of the total average of medium completion and high completion, it shows that the motivation of training participants in developing innovative learning processes, designing innovative learning programs according to the demands of the independent curriculum, innovating teaching modules based on innovative learning models, and becoming professional teachers according to the demands of the independent curriculum has increased.